Ein zeitbeschränkter Test zur schnellen Erkennung von Schülerfehlern durch Junglehrkräfte – Qualitative Merkmale zur Schwierigkeitsbestimmung von Items (mathematica didactica, 2021)
In order to promote learning opportunities, a fast recognition of students’ errors is a necessary prerequisite for a constructive approach to students’ errors. In the time-limited test for identifying students’ errors from the TEDS-FU study, early career teachers were requested to recognize typical students’ errors under time constraints. In the two tests for primary and secondary teachers, two characteristics could be identified as difficulty generating aspects, focusing the perspective of mathematics didactics and the psychology of perception. The identified characteristics can be used as an analysis tool for a new test for fast recognition of students’ errors in the design process as well as the basis for the explanation of item difficulty.